A formação e a demanda do mercado de trabalho do contador a região metropolitana de Porto Alegre - RS - Pires, Charline Barbosa (Universidade do Vale do Rio do Sinos, 2008)
This study examines the synthesis between the education and the demand for the Account professional labor market in the urban area of Porto Alegre, Brazil. Therefore, using the techniques of the Bivariate and Multivariate Descriptive Statistics, it analyses 939 employment public offers collected form January to September 2007 in Zero Hora newspaper and in the professional replacement site called Manager, as well as the curriculum and the characteristics of 9 Account courses from Colleges in and around Porto Alegre. The investigation of the employ offers reveal that the applicants must have a large set of knowledge, skills and attitudes, but the demand for candidates that have previous professional experience and familiarity related “Financial Accounting and Taxes Legislation” is high, since this group of competences has been identified as the most prized by the labor market. By their turn, the results of the analysis of the educational institutions curriculum reveal that, with the exception of the “Foreig
Keywords: contadores; educação contábil; mercado de trabalho; accountants; accounting education; labor market; Ciências Sociais Aplicadas